2018
DOI: 10.1002/mop.31025
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a resonator based metamaterial for sensor applications

Abstract: A resonator based metamaterial for sensor application is studied in this paper. The resonator is encompassed by a partial ground plane and excited by a microstrip feed‐line. As the resonator, partial ground frame, and the feeding transmission line are on the same microstrip, the measurement can be executed by using the common laboratory facility instead of using the waveguide. The proposed metamaterial occupies a compact size of 20 × 20 mm2 and is imprinted on a low‐cost FR4 substrate. The substrate has a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…When the sample relative permittivity increases, the resonance frequency decreases from 4.9 to 3.7 GHz, whereas in the same condition, this value is shifted [8]. As illustrated in Fig.…”
Section: Measurement Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…When the sample relative permittivity increases, the resonance frequency decreases from 4.9 to 3.7 GHz, whereas in the same condition, this value is shifted [8]. As illustrated in Fig.…”
Section: Measurement Resultsmentioning
confidence: 82%
“…As illustrated in Fig. 11, for changing the relative permittivity, the resonance values are between −50 and −49 dB in the proposed configuration, therefore, it can be said that the resonance value is almost fixed with changing the relative permittivity, while in the proposed sensor of [8], values of resonance change from −41 to −21 dB in the operational frequency. A sample with the grater dielectric constant has a larger downshift of the resonance frequency.…”
Section: Measurement Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Metamaterials have been utilised in a wide range of application fields, for instance, sensor, Specific Absorption Rate (SAR) reduction, satellite application, terahertz frequency application, superconductor, optical cloaking, microwave application, etc. 1 – 4 . Nevertheless, these series of recent studies have indicated that the application fields are different from each other, and the distinctive properties of the metamaterial allowed the researchers to obtain remarkable results.…”
Section: Introductionmentioning
confidence: 99%